1996
DOI: 10.1002/(sici)1520-670x(199605)8:4<201::aid-jtra2>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

Serum zinc and plasma lipoproteins in elderly women: Findings from the nun study

Abstract: Supplementation with zinc has been associated with changes in lipoprotein levels in prior studies. The purpose of this study was to define further the relationship between serum zinc and plasma total cholesterol, low density lipoprotein (LDL) cholesterol, high density lipoprotein (HDL) cholesterol, and triglycerides. This study was conducted in a homogeneous population of elderly women who were not taking zinc supplements. Fasting blood samples were drawn from 87 women, 77–99 years old. Serum zinc concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…However, multivariate analysis revealed that serum zinc concentrations were weakly associated with serum HDL cholesterol and DBP, with lesser contributions from age, serum triglycerides and gender. Tully and colleagues 57 have previously shown that serum zinc concentrations are positively related to LDL cholesterol concentrations in a female population, and they have proposed that both zinc and cholesterol may be related to a third factor, possibly dietary intake of red meat. Jossa et al 58 have previously found no signi¢cant association between serum selenium and several coronary risk factors, including: triglycerides, HDL cholesterol, systolic and DBP, age and BMI.…”
Section: Trace Element Status In Obesitymentioning
confidence: 99%
“…However, multivariate analysis revealed that serum zinc concentrations were weakly associated with serum HDL cholesterol and DBP, with lesser contributions from age, serum triglycerides and gender. Tully and colleagues 57 have previously shown that serum zinc concentrations are positively related to LDL cholesterol concentrations in a female population, and they have proposed that both zinc and cholesterol may be related to a third factor, possibly dietary intake of red meat. Jossa et al 58 have previously found no signi¢cant association between serum selenium and several coronary risk factors, including: triglycerides, HDL cholesterol, systolic and DBP, age and BMI.…”
Section: Trace Element Status In Obesitymentioning
confidence: 99%